2018
DOI: 10.1007/s11356-018-2153-5
|View full text |Cite
|
Sign up to set email alerts
|

Bird diversity and dissimilarity show contrasting patterns along heavy metal pollution gradients in the Urals, Russia

Abstract: The effects of industrial pollution on bird diversity have been widely studied using traditional diversity measures, which assume all species to be equivalent. We compared species richness and Shannon index with distance-based measures of taxonomic, functional, and phylogenetic diversity (the abundance-weighted mean nearest taxon distances), which describe within-community dissimilarity at terminal branches. Analysis of dissimilarity can shed light on the processes underlying community assembly, i.e., environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…A similar study found bird diversity declined with increasing distance from several stone crusher units, which correlated with changes in the air pollutants that were quantified in our study (Saha & Padhy, 2011). Bird densities and diversity also correlate with heavy metal pollution along a pollution gradient (Belskii & Mikryukov, 2018) and proximity to copper smelter sites (Eeva et al, 2012). Despite these past studies, our fine-scale measures of NO 2 and UFPs across our study site have allowed us to disentangle and evaluate the effects of air pollution versus other factors (i.e., vegetation) on bird communities.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study found bird diversity declined with increasing distance from several stone crusher units, which correlated with changes in the air pollutants that were quantified in our study (Saha & Padhy, 2011). Bird densities and diversity also correlate with heavy metal pollution along a pollution gradient (Belskii & Mikryukov, 2018) and proximity to copper smelter sites (Eeva et al, 2012). Despite these past studies, our fine-scale measures of NO 2 and UFPs across our study site have allowed us to disentangle and evaluate the effects of air pollution versus other factors (i.e., vegetation) on bird communities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some metals are highly toxic even at low concentrations (Zahir et al, 2005). Heavy metal pollution is one of the most important threats to marine (Ling et al, 2018), freshwater (Abdelhady et al, 2019), and terrestrial (Belskii and Mikryukov, 2018) biodiversity. Exposure to heavy metals has resulted in growth and developmental abnormalities, detrimental effects on productivity, and death in animals (Migliarini et al, 2005;Burki, 2012;Hargitai et al, 2016;Pavlaki et al, 2016;Zeng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, functional diversity (FD) and phylogenetic diversity (PD) have been increasingly advocated to quantify assemblage structures, which are deemed to better reflect the underlying ecological processes than species richness ( Cadotte et al 2011 ; Srivastava et al 2012 ). For example, environmental pollution affects assembly processes and results in functionally and phylogenetically non-random communities ( Belskii and Mikryukov 2018 ). Species richness, functional diversity, and phylogenetic diversity showed different patterns along the altitudinal gradient ( Dehling et al 2014 ).…”
mentioning
confidence: 99%
“…Birds play an important role in ecosystem function and are strongly sensitive to the changes in their environment, which made them ideal taxa to be used in exploring the assembly processes and in assessing the effects of environmental changes on biological communities ( Naithani and Bhatt 2012 ; Chen et al 2019 ; Penjor et al 2021 ). It is commonly argued that metal pollution can pose stresses for birds, such as the decline of bird density, species richness, and diversity ( Eeva et al 2012 ; Belskii and Mikryukov 2018 ). In addition, trace metals pollution might also affect the assembly process of bird communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation